Dinamika Konflik dalam Pembangunan Bandara Surabaya II di Kabupaten Nagekeo, Nusa Tenggara Timur - Jubaidah, Arni Fazira; Sayrani, Laurensius P.; Andayana, Made N. D. (Universitas Pahlawan Tuanku Tambusai, 2025)
The construction of the airport will be built in Mbay, Regency Nagekeo will be called Surabaya II Airport which is located in Tonggurambang Village. In addition, Mbay occupies a strategic position because it is located in the middle of Flores Island and has been designated as the center of the National Strategy Area. The airport was planned to be built on the land of a former Japanese military base in 1944 and then designated as a pioneer airport in 1975. This qualitative research uses a case study approach, data collection is done through observation, interviews and documentation. It aims to find out the main causes of conflict in the form of differences in interests in determining the location of the airport, land ownership status and community land acquisition. Conflicts in airport development have a complicated and complex nature involving three main actors, namely the local government, the Indonesian national army, and the local community. Although the construction of this airport is seen as strategic for economic development and regional tourism, the construction of Surabaya II airport in Nagekeo district has not yet been realized.